A Retrospective Study on English Teachers’ Strategies to Increase Students’ Vocabulary Mastery - Lianty Putri; Fatmawaty Fatmawaty; Erikson Saragih; Madina Madina (Universitas Negeri Semarang, 2022)
Various teaching methods and techniques have been the focus of numerous studies on teaching strategies used to increase students' vocabulary understanding. Few studies, however, have looked at the methods teachers employ to increase their students' vocabulary mastery through retrospective study. This retrospective review of the study collected various types of teaching strategies that benefit teachers. Researchers combined a descriptive method with a qualitative research approach with a questionnaire design for this study. Instruments in this research is a survey in the form of google form. The types of questions in previous research surveys used many types of closed-ended questions in the form of statements. In contrast, the types of questions in this study used many open-ended questions that produced answers consisting of many ideas. Fifteen English teachers who teach English in Medan are the subjects of this study. The result of this research is the strategies used by teachers in teaching student vocabulary mastery are very diverse depending on students' and teachers' abilities. The more diverse the teacher's teaching strategies, the more successfully students will learn new words. The teaching strategy is then divided into three, namely preparation, practice, and evaluation strategies. In the end, it is anticipated that the findings of this study will help teachers succeed in developing their students’ vocabulary mastery.Various teaching methods and techniques have been the focus of numerous studies on teaching strategies used to increase students' vocabulary understanding. Few studies, however, have looked at the methods teachers employ to increase their students' vocabulary mastery through retrospective study. This retrospective review of the study collected various types of teaching strategies that benefit teachers. Researchers combined a descriptive method with a qualitative research approach with a questionnaire design for this study. Instruments in this research is a survey in the form of google form. The types of questions in previous research surveys used many types of closed-ended questions in the form of statements. In contrast, the types of questions in this study used many open-ended questions that produced answers consisting of many ideas. Fifteen English teachers who teach English in Medan are the subjects of this study. The result of this research is the strategies used by teachers in teaching student vocabulary mastery are very diverse depending on students' and teachers' abilities. The more diverse the teacher's teaching strategies, the more successfully students will learn new words. The teaching strategy is then divided into three, namely preparation, practice, and evaluation strategies. In the end, it is anticipated that the findings of this study will help teachers succeed in developing their students’ vocabulary mastery.